Bone quality in patients with chronic osteomyelitis of the foot according to computed tomography data - G. V. Diachkova; Yu. L. Mitina; N. M. Klyushin; S. M. Aleksandrov; T. A. Larionova; A. G. Mikhailov (Вестник рентгенологии и радиологии, 2016)
Objective: to study radiographic morphological changes in the bones of the foot in its chronic osteomyelitis and to develop indicators for assessing bone quality.Material and methods. The results of foot bone multislice computed tomography (MSCT) using 64 detector rows were analyzed in 29 patients with chronic osteomyelitis of the talus, calcaneus, and midfoot bones.Results. Radiographic changes in the talus and calcaneus in chronic osteomyelitis were characterized by pronounced polymorphism and accompanied by the lower density of the talus and calcaneus and by the lack of their organotypic structure. In a number of cases, the organotypic structure was entirely absent in the calcaneus along with marked anatomical changes (a defect). In these cases, the talus also undergoes considerable changes; however, its density does not decrease to more than 200 HU. Based on an analysis of the findings on the specific features of the architectonics of the talus and calcaneus and their density, the criteria for assessing bone quality, which allow estimation of the magnitude of radiographic morphological changes in the foot bones, were proposed to choose a method for treatment and rehabilitation.Conclusion. The use of the proposed criteria for assessing bone quality indicated moderate, significant, and serious quality defects in 4, 5, and 20 patients, respectively. The findings should be kept in mind when choosing a method for treatment and rehabilitation measures.